Comparison of Postoperative Neck Pain and Discomfort, Swallowing Difficulty, and Voice Change After Conventional Open, Endoscopic, and Robotic Thyroidectomy: A Single-Center Cohort Study - Ha, Tae Kwun; Kim, Dong Wook; Park, Ha Kyoung; Shin, Gi Won; Heo, Young Jin; Baek, Jin Wook; Lee, Yoo Jin; Choo, Hye Jung; Kim, Do Hun; Jung, Soo Jin; Park, Ji Sun; Moon, Sung Ho; et al. (Frontiers in Endocrinology, 2018)
Background: The objective of this study was to compare the postoperative neck pain and discomfort, swallowing difficulty, and voice change after conventional open thyroidectomy (COT), endoscopic thyroidectomy (ET), or robotic thyroidectomy (RT) performed by a single surgeon. Methods: From January 2013 to December 2017, 254 patients underwent COT, ET, or RT performed by a single surgeon and completed a postoperative symptom survey conducted in the outpatient clinic by three nurses. The survey collected information on postoperative neck pain and discomfort, swallowing difficulty, and voice change. Results: Of the 254 patients, 169 underwent COT, 32 underwent ET, and 53 underwent RT. The mean age in the COT, ET, and RT groups was 50.1, 44.5, and 41.6 years, respectively. The mean interval between thyroidectomy and survey in the COT, ET, and RT groups was 42.7, 50.2, and 9.2 months, respectively. Postoperative neck pain was significantly higher in the ET and RT groups than in the COT group (p=0.026). The average neck impairment index score in the RT group was significantly higher than that in the COT group (p <0.001). There were no significant differences in pain scale scores, swallowing difficulty, swallowing impairment index, voice change, and voice hand index among the three groups. Conclusions: There were no significant differences in postoperative voice change or swallowing difficulty among the COT, ET, and RT groups, whereas neck pain and discomfort were more common after ET and RT than COT.